Regulation, genomics, and clinical characteristics of cuproptosis regulators in pan-cancer - Zhou, Cankun; Li, Chaomei; Zheng, Yuhua; Huang, Xiaobin (Frontiers in Oncology, 2022)
Background: Cuproptosis, a copper-dependent controlled cell death, is a novel form of cell death that differs from known cell death mechanisms; however, its overall regulation in cancer remains elusive. Methods: Multiple open-source bioinformatic platforms were used to comprehensively elucidate the expression levels, prognostic efficiency, potential biological functions, genomic and epigenetic characteristics, immune microenvironment and drug sensitivity of cuproptosis regulators (ATP7A, ATP7B, DLAT, DLD, FDX1, GLS, LIAS, LIPT1, MTF1, NLRP3, PDHA1, PDHB and SLC31A1) in pan-cancer. Results: Cuproptosis-related genes (CRGs) were upregulated in most cancers tested. In KIRC, KIRP, LGG, MESO and PCPG, most highly expressed CRGs predicted a better prognosis, while poorer prognosis in patients with ACC, LIHC and UCEC. Pathway analysis confirmed that cuproptosis regulators were associated with the metabolism-related pathways. The expression of MTF1, NLRP3, and SLC31A1 was positively related with ImmuneScore, StromalScore, and ESTIMATEScore in almost all types of tumor, whereas ATP7B, DLAT, DLD, LIAS, PDHA1 and PDHB were significantly negatively correlated with the scores. In addition, CRGs was significantly correlated with RNA stemness score (RNAss), DNA stemness score (DNAss), microsatellite instability (MSI) and tumour mutational burden (TMB). The expression of ATP7A, ATP7B, LIAS, DLAT was significantly positively correlated with the drug sensitivity of Docetaxel. ATP7A, LIAS, and FDX1 were significantly negatively correlated with the drug sensitivity of UNC0638, XMD13−2, YM201636, and KIN001−260. Conclusions: The altered genomic and clinical characteristics of cuproptosis regulators were comprehensively elucidated, providing a preliminary basis for understanding the functions of cuproptosis in pan-cancer.